Evaluation of Growth and Yield of Four Maize ( Zea mays L.) Cultivars Under Northern State Conditions - محمد، جلال أحمد التوم (جامعة السلام, 2018)
أجريت هذه الدراسة بالمزرعة التجريبية لكلية العلوم الزراعية جامعة دنقلا السليم في الموسم الصيفي2016. تم استخدام تصميم القطاعات العشوائية الكاملة بأربعة مكررات وذلك لتقييم النمو والإنتاجية لأربعة أصناف من الذرة الشامية تحت ظروف الولاية الشمالية. أوضح تحليل التباين وجود فروق معنوية بين أصناف الذرة الشامية الأربعة في كل مكونات النمو الخضري والثمري والتي تتمثل في طول النبات، سمك النبات، عدد الأوراق/ النبات، عدد الأيام اللازمة لظهور 50% من النورة المذكرة، عدد الأيام اللازمة لظهور 50% من النورة المؤنثة وعدد الأيام اللازمة للنضج. أيضا كانت هنالك اختلافات معنوية بين أصناف الذرة الشامية في الإنتاجية ومكوناتها باستثناء عدد لصفوف/ الكوز والتي كانت غير معنوية، والتي تتمثل في طول الكوز، عدد البذور/ الصف، عدد البذور/ الكوز، وزن الألف حبة وإنتاجية الحبوب.
The current study was conducted at the Demonstration Farm of the Faculty of Agricultural Sciences –University of Dongola-El Seleim-Sudan ( Latitude 19˚ 11˝ N and Longitude 30˚ 29˝ E and altitude 227m ASL) during the summer season 2016. A Randomized Complete Block Design (RCBD) with four replications was used to compare the vegetative growth and yield attributes of four maize cultivars (Hudeiba-1, Hudeiba-2, Mugtama-45 and Balady). The experiment was. The results revealed significant differences among maize cultivars in all vegetative and reproductive growth parameters studied namely., Plant height, stem diameter, number of leaves / plant, days to 50% tasselling, days to 50% siliking and days to maturity. Also, differences among maize cultivars was significant for yield and yield components characters with the exception of number of rows/ cob which exhibited no significant differences, these included cob length, , number of seeds/row, number of seeds/cob, 100- seed weight and grains yield.
Keywords: المزارع -- النباتات -- النمو -- النشاط الزراعى -- الحياة الاقتصادية